Corruption Perception Studies and Anti-Corruption in Nigeria (Glocalism: Journal of Culture, Politics and Innovation, 2016)
Perception studies of corruption have proliferated in the last decade. However, there is a lingering controversy over the proper us of the outputs from such studies to benefit anti-corruption efforts. Against this backdrop, these paper reviews the theoretical context of the perception studies of corruption and their justifications. It examined key perception studies of corruption at the global, regional and national levels in relation to Nigeria and discusses key issues associated with them. These include controversies around the definition of corruption, methodological issues such as the reliability of the perception approach to the study of corruption, possibilities of cross country comparisons, the connections between global, regional and local anticorruption studies and the issue of how such studies and rankings reflect power relations. The paper argues that perception studies will be significant and effective to the extent that elites and government officials continue to take the opinion and perception of citizens and other stakeholders seriously.
Keywords: Anti-Corruption; Governance reform; performance indicators; Perception studies; Nigeria